The Effect of Marketing Strategy Implementation and Customer Behavior on Satisfaction and Trust and Its Implication on Loyalty in Non Recipient Health Insurance Participants - Surjono, Welly; Jusuf, Eddy; Suryana, Popo (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2024)
Purpose – The purpose of this study was to find out, study and analyze the implementation of marketing strategies and customer behavior on satisfaction and trust and their implications for the loyalty of BPJS Kesehatan participants who are not recipients of contribution assistance. Methodology/approach – The research method used is a survey method with quantitative research type, descriptive-verification research nature. The research sample was 400 BPJS Health participants who did not receive contribution assistance, this study used purposive and proportional clustered random sampling methods. In addition, the analysis method used is Structural Equation Modelling (SEM) analysis. Findings – The results of the study concluded that there was a significant influence from the implementation of marketing strategies and customer behavior on satisfaction by 76.15 percent, and there was a significant effect from the implementation of marketing strategies and customer behavior on trust by 78.24 percent, and there was a significant effect from satisfaction and trust in loyalty of 82.78 percent. Novelty/value – Marketing strategy consisting of target market and marketing mix, combined with consumer behaviour consisting of customer characteristics and customer psychology will have an impact on satisfaction and trust and have implications for loyalty.